Thematic Layers of Genomic Susceptibility for Conservation Monitoring - Andrew N. Black; Jong Yoon Jeon; Andrew J. Mularo; Natalie M. Allen; Erangi Heenkenda; Julia C. Buchanan‐Schwanke; John W. Bickham; Zachary E. Lowe; J. Andrew DeWoody (Molecular Ecology, 2025)
Population genomics has great potential to inform applied conservation management and associated policy. However, the bioinformatic analyses and interpretation of population genomic datasets can be daunting and difficult to convey to nonspecialists, including on‐the‐ground conservationists that work with many state, federal and international agencies. We think that individual population genomic metrics of interest can be interpolated and ultimately distilled into thematic GIS layers that represent spatiotemporal genomic potential (or conversely, susceptibility) in conservation monitoring. As examples relevant to ongoing conservation efforts, we use introgressive hybridisation and individual heterozygosity to illustrate a conceptual approach for mapping population genomic susceptibility. The general framework of thematic layers could be extended to integrate key genomic metrics (e.g., runs of homozygosity and genomic load) that are relevant to many conservation efforts.